Effect of Smoking Application on the Quality of Local Timor Corn - Jefrianus Nino; Eduardus Y. Neobeni; Claudia S. Nule (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Corn is one of the most widely cultivated plants in Indonesia and is used as a staple food by several people, especially in the province of East Nusa Tenggara. The way to store corn is done by farmers, namely smoking. Fumigation is done by burning wood in the smoking room (kitchen). Fumigation is carried out with the intention of preserving corn by utilizing a heat source that comes from the smoke from burning wood or other materials. The purpose of this study was to determine changes in water content changes during the smoking process using plant materials and to determine the quality of local Timor corn. Based on the results of the study, the average ambient temperature was 30.43ºC, the average RH was 81.76%, with an average initial moisture content of 18.76% wb was able to reduce the water content of local Timor corn to 11% wb (using  Schleicera oleosa), 10.5% wb (Hyptis suaveolens), and 10.2 (Chromolaena odorata), average reducing sugars 0.52% wb, average protein content 7.82% wb, average carbohydrates of 7.59% wb, and average fat of 5.35% wb. Keywords:   Corn, Nutrition Value, Smoking, Soluble Solid, Timor